2020
DOI: 10.1590/1808-057x201909110
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for bitcoins in light of IFRS and tax aspects

Abstract: This essay presents recommendations in regard to accounting for operations that involve bitcoins, in compliance with the International Financial Reporting Standards (IFRS), and analyzes their main tax aspects. There is no specific pronouncement on the part of the International Accounting Standards Board (IASB) or from the Brazilian Accounting Pronouncements Committee (CPC) regarding the accounting treatment to be applied in operations that use these currencies. Bitcoin is of interest to economists as a virtual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 10 publications
0
10
0
6
Order By: Relevance
“…The first miner to successfully do so and have her block validated by the users, known as nodes, receives a number of newly minted bitcoins in reward. This procedure allows the blockchain to function without any trust between the parties involved (Pelucio-Grecco et al, 2020).…”
Section: Blockchain Technologymentioning
confidence: 99%
“…The first miner to successfully do so and have her block validated by the users, known as nodes, receives a number of newly minted bitcoins in reward. This procedure allows the blockchain to function without any trust between the parties involved (Pelucio-Grecco et al, 2020).…”
Section: Blockchain Technologymentioning
confidence: 99%
“…O primeiro minerador a fazer isso com sucesso e ter seu bloco validado pelos usuários, conhecido como nós, recebe uma série de bitcoins recém-cunhadas como recompensa. Esse procedimento permite que o blockchain funcione sem qualquer confiança entre as partes envolvidas (Pelucio-Grecco et al, 2020).…”
Section: Tecnologia Blockchainunclassified
“…In contrast to Ram's (2016) analysis that focuses on bitcoin measurement, in the research of Pelucio-Grecco et al (2020) analyze the characteristics of Bitcoin that have been identified by Ram (2016) to select and apply accounting policies that comply with IAS 8. They identify what standard treats events that are most similar to bitcoin.…”
Section: Crypto-assets As Assetsmentioning
confidence: 99%